Composite catalyst and Fischer-Tropsch synthesis reaction method

By using a composite catalyst supported by cobalt element on an oxide support and molecular sieve in the Fischer-Tropsch synthesis reaction, the problem of insufficient selectivity of diesel fractions in the prior art is solved, and the effect of efficient conversion of synthesis gas into diesel fractions is achieved.

CN119114140APending Publication Date: 2024-12-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310698349.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The target product selectivity in the existing Fischer-Tropsch synthesis reaction is low, especially the diesel fraction is insufficient, which fails to effectively improve the performance of the middle fraction.

Method used

Using a composite catalyst, the catalyst is supported by cobalt elements in an oxide support and molecular sieve, and is prepared by impregnation, calcination, etc., and is used in Fischer-Tropsch synthesis reaction to optimize the content of cobalt elements and the weight ratio of support/molecular sieve to improve the diesel fraction Selective.

Benefits of technology

It has achieved efficient conversion of syngas into diesel fractions, significantly improving the selectivity of diesel fractions and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention relates to a composite catalyst and a Fischer-Tropsch synthesis reaction method. The composite catalyst comprises a cobalt element, a carrier and a molecular sieve, the cobalt element is loaded in the carrier and / or the molecular sieve; wherein the carrier is an oxide carrier; the weight ratio of the carrier to the molecular sieve is 0.1-15; based on the total amount of the composite catalyst, the content of the cobalt element is 5-40 wt%. The composite catalyst disclosed by the invention is used in Fischer-Tropsch synthesis and has the characteristics of high activity and high selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a composite catalyst and a Fischer-Tropsch synthesis reaction method. Background Art

[0002] The Fischer-Tropsch synthesis technology can be used to convert non-petroleum carbon resources such as coal, natural gas, and biomass into liquid fuels and high-value chemicals, which is beneficial to alleviating the increasingly serious energy crisis and environmental problems and providing strategic guarantees for national energy security. The development of highly active, highly selective, and highly stable catalysts is the key to the application of this technology.

[0003] In view of the low selectivity of the target product in the traditional Fischer-Tropsch synthesis reaction, researchers can use a relay catalytic strategy to achieve the coupling of the Fischer-Tropsch reaction and the catalytic cracking reaction by using a composite Fischer-Tropsch catalyst and a molecular sieve with cracking / isomerization / hydrogenolysis catalytic function, thereby significantly improving the selectivity of liquid fuels and high-value chemicals such as low-carbon olefins, aromatics, high-carbon alcohols and other oxygen-containing compounds, and providing a broad idea for the development of efficient synthesis gas conversion catalysts. Patent CN111266131A provides a composite catalyst composed of a metal oxide with Fischer-Tropsch synthesis performance and a molecular sieve with acid catalytic performance, which can improve the selectivity of low-carbon olefins (68.76%) while maintaining a high conversion rate of synthesis gas (86.75%). Patent CN113289677B provides a multiphase metal catalyst for synthesizing aromatics from synthesis gas, which is composed of a mechanical mixture of a silicon-aluminum molecular sieve and a multiphase metal oxide (cerium oxide-zirconia and zinc oxide-zirconia), and can simultaneously achieve a CO conversion rate of 53.75% and an aromatics selectivity of 81.17%. In the patent CN111250075B published by Dalian Institute of Chemical Physics of Chinese Academy of Sciences, the composite catalyst obtained by physically mixing metal oxide of spherical ZnGa2O4 nanoparticles and molecular sieves shows good stability in the reaction of synthesizing light olefins from syngas. After 250h of reaction, the selectivity of light olefins can still be maintained at 75-80%, and the methane selectivity is less than 5%. However, there is no report on how to improve the middle fraction, especially the diesel fraction, in the prior art. Summary of the invention

[0004] The object of the present invention is to provide a catalyst for use in a Fischer-Tropsch synthesis reaction to improve the selectivity of an intermediate fraction (especially a diesel fraction).

[0005] In order to achieve the above object, the first aspect of the present invention provides a composite catalyst, which comprises a cobalt element, a carrier and a molecular sieve; the cobalt element is loaded in the carrier and / or the molecular sieve; wherein the carrier is an oxide carrier; the weight ratio of the carrier to the molecular sieve is 0.1 to 15; based on the total amount of the composite catalyst, the content of the cobalt element is 5 to 40wt%. The composite catalyst of the present invention can realize the efficient conversion of synthesis gas into diesel fraction, and has good application prospects.

[0006] Optionally, the weight ratio of the carrier to the molecular sieve is 0.1 to 12, preferably 0.2 to 6; based on the total amount of the composite catalyst, the content of cobalt element is 5 to 32 wt%, preferably 8 to 25 wt%.

[0007] Optionally, the carrier is selected from at least one of SiO2, TiO2 and Al2O3; the molecular sieve is selected from at least one of NaY molecular sieve, ZSM-5 molecular sieve, ZSM-22 molecular sieve and SBA-15 molecular sieve, preferably NaY molecular sieve; Optionally, the NaY molecular sieve has a SiO2 / Al2O3 ratio of 4 to 10 and a specific surface area of ​​500 to 800 m 2 / g.

[0008] Optionally, the composite catalyst is a granular catalyst, and the particle size of the granular catalyst is 10 to 80 μm.

[0009] Optionally, the composite catalyst comprises a supported catalyst and the molecular sieve; the supported catalyst comprises the carrier and the cobalt element supported in the carrier.

[0010] Optionally, the preparation method of the composite catalyst includes: impregnating the carrier and / or the molecular sieve in a solution containing a cobalt salt to obtain an impregnated material; aging the impregnated material and then drying and performing a first calcination treatment; or, impregnating the carrier or the molecular sieve in a solution containing a cobalt salt to obtain an impregnated material; aging the impregnated material and then drying and performing a second calcination treatment to obtain a loaded material; mixing the loaded material with the unloaded carrier or the molecular sieve and then performing a grinding treatment and a molding treatment;; Optionally, the cobalt salt is selected from at least one of cobalt nitrates, sulfates, halides, nitrites, ammonium salts and acetates; preferably at least one of nitrates, nitrites and acetates.

[0011] Optionally, the impregnation is saturated impregnation; the aging conditions include: temperature of 30-60°C, preferably 35-45°C; time of 6-48h, preferably 12-24h; the drying conditions include: temperature of 80-150°C, preferably 90-120°C; time of 6-48h, preferably 12-24h; the first calcination treatment is carried out in a nitrogen or air atmosphere, and the conditions of the first calcination treatment include: temperature of 300-600°C, preferably 350-450°C; time of 2-10h, preferably 4-6h; the second calcination treatment is carried out in a nitrogen or air atmosphere, and the conditions of the second calcination treatment include: temperature of 300-600°C, preferably 350-450°C; time of 2-10h, preferably 4-6h.

[0012] Optionally, the preparation method of the composite catalyst includes: mixing the carrier and / or the molecular sieve with a cobalt source and grinding the mixture to obtain a mixed material; melting the mixed material and performing a third calcination treatment; or, mixing the carrier or the molecular sieve with a cobalt source and grinding the mixture to obtain a mixed material; melting the mixed material and performing a fourth calcination treatment to obtain a loaded material; mixing the loaded material with the unloaded carrier or the molecular sieve and performing a grinding treatment and a molding treatment; optionally, the cobalt source is a solid cobalt source, and the cobalt source is selected from at least one of cobalt nitrates, sulfates, halides, nitrites, ammonium salts and acetates; preferably at least one of nitrates, nitrites and acetates.

[0013] Optionally, the conditions for the drying treatment include: a temperature of 80 to 150°C, preferably 90 to 120°C; a time of 6 to 48 hours, preferably 12 to 24 hours; the calcination atmosphere of the third calcination treatment is one of nitrogen, air and a reducing atmosphere; the conditions for the third calcination treatment include: a temperature of 300 to 600°C, preferably 350 to 450°C; a time of 2 to 8 hours, preferably 4 to 6 hours; the calcination atmosphere of the fourth calcination treatment is one of nitrogen, air and a reducing atmosphere; the conditions for the fourth calcination treatment include: a temperature of 300 to 600°C, preferably 350 to 450°C; a time of 2 to 8 hours, preferably 4 to 6 hours.

[0014] A second aspect of the present invention provides a method for Fischer-Tropsch synthesis reaction, wherein the catalyst used in the method for Fischer-Tropsch synthesis reaction includes the aforementioned composite catalyst.

[0015] Optionally, the Fischer-Tropsch synthesis reaction method comprises: mixing the catalyst with quartz sand and loading the mixture into a reactor, reducing the catalyst in situ, and introducing synthesis gas for synthesis reaction; wherein the synthesis gas comprises H2 and CO, and the volume ratio of H2 to CO is 1 to 2, and the conditions of the synthesis reaction include: temperature of 200 to 250°C, pressure of 1.5 to 4 MPa, and volume space velocity of 1000 to 10000 h -1 .

[0016] Optionally, the reducing gas used in the in-situ reduction is hydrogen, and the temperature of the in-situ reduction is 300-500°C.

[0017] Through the above technical scheme, the composite catalyst provided by the present invention includes cobalt element, a carrier and a molecular sieve, wherein the cobalt element is loaded in the carrier and / or the molecular sieve in a loaded form. When the composite catalyst of the present invention is used for the Fischer-Tropsch synthesis reaction, it has the characteristics of high activity and high selectivity, can efficiently convert synthesis gas into diesel fraction, and has good application prospects.

[0018] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0020] The first aspect of the present invention provides a composite catalyst, which includes a cobalt element, a carrier and a molecular sieve; the cobalt element is loaded in the carrier and / or the molecular sieve; wherein the carrier is an oxide carrier; the weight ratio of the carrier to the molecular sieve is 0.1 to 15; based on the total amount of the composite catalyst, the content of the cobalt element is 5 to 40wt%.

[0021] The composite catalyst provided by the present invention comprises a cobalt element, a carrier and a molecular sieve, wherein the cobalt element is loaded in the carrier and / or the molecular sieve in a loaded form. When the composite catalyst of the present invention is used for the Fischer-Tropsch synthesis reaction, it has the characteristics of high activity and high selectivity, can efficiently convert synthesis gas into a diesel fraction, and has good application prospects.

[0022] According to the present invention, the weight ratio of the carrier to the molecular sieve can be 0.1 to 12, preferably 0.2 to 6; based on the total amount of the composite catalyst, the content of cobalt element can be 5 to 432wt%, preferably 8 to 25wt%. The present invention can further improve the selectivity of syngas to diesel fraction in the Fischer-Tropsch synthesis reaction by optimizing the content of cobalt element and the weight ratio of the carrier to the molecular sieve.

[0023] According to the present invention, the carrier can be selected from at least one of SiO2, TiO2 and Al2O3; the molecular sieve can be selected from at least one of NaY molecular sieve, ZSM-5 molecular sieve, ZSM-22 molecular sieve and SBA-15 molecular sieve, preferably NaY molecular sieve; optionally, the NaY molecular sieve has a SiO2 / Al2O3 ratio of 4 to 10 and a specific surface area of ​​500 to 800 m 2 / g.

[0024] In a preferred embodiment of the present invention, the composite catalyst comprises a supported catalyst and the molecular sieve; the supported catalyst comprises the carrier and the cobalt element supported in the carrier. In this preferred embodiment, the cobalt element is supported on an oxide carrier, and then the oxide carrier supported with the cobalt element is mixed with the molecular sieve to obtain a composite catalyst. Compared with other loading methods of the cobalt element, this embodiment can effectively promote the conversion of CO, while improving the selectivity of the intermediate fraction of the Fischer-Tropsch product (especially the diesel fraction).

[0025] Optionally, the composite catalyst is a granular catalyst, and the particle size of the granular catalyst is 10 to 80 μm.

[0026] The preparation method of the composite catalyst of the present invention can be prepared in a variety of ways. For example, a supported cobalt-based catalyst can be prepared first, the catalyst powder and the molecular sieve powder are mixed in a certain proportion, and then ground evenly in a mortar, and then tableted and crushed to obtain a final catalyst; or, a supported cobalt-based catalyst can be prepared first, the catalyst powder and the molecular sieve powder are respectively tableted and crushed, and then two particles of the same mesh size are physically mixed in a certain proportion to obtain a final catalyst; or, an oxide carrier powder and a molecular sieve powder can be mixed in a certain proportion, and then ground evenly in a mortar, and then tableted and crushed to obtain a composite carrier, and then cobalt is loaded to obtain the final catalyst.

[0027] In an exemplary embodiment of the present invention, the loading method of the cobalt element can be carried out by an impregnation method, and the preparation method of the composite catalyst includes: placing the carrier and / or the molecular sieve in a solution containing a cobalt salt for impregnation to obtain an impregnated material; aging the impregnated material and performing a drying treatment and a first calcination treatment; or, placing the carrier or the molecular sieve in a solution containing a cobalt salt for impregnation to obtain an impregnated material; aging the impregnated material and performing a drying treatment and a second calcination treatment to obtain a loaded material; mixing the loaded material with the unloaded carrier or the molecular sieve and performing a grinding treatment and a molding treatment; optionally, the cobalt salt is selected from at least one of nitrates, sulfates, halides, nitrites, ammonium salts and acetates of cobalt; preferably at least one of nitrates, nitrites and acetates. The preparation method has the characteristics of good reliability, strong repeatability and high universality.

[0028] According to the present invention, the impregnation is preferably saturated impregnation; the aging conditions may include: a temperature of 30-60°C, preferably 35-45°C; a time of 6-48h, preferably 12-24h; the drying conditions may include: a temperature of 80-150°C, preferably 90-120°C; a time of 6-48h, preferably 12-24h; the first calcination treatment may be carried out in a nitrogen or air atmosphere, and the conditions of the first calcination treatment may include: a temperature of 300-600°C, preferably 350-450°C; a time of 2-10h, preferably 4-6h; the second calcination treatment may be carried out in a nitrogen or air atmosphere, and the conditions of the second calcination treatment may include: a temperature of 300-600°C, preferably 350-450°C; a time of 2-10h, preferably 4-6h.

[0029] According to an exemplary embodiment of the present invention, the cobalt element can be loaded by a melting method, and the preparation method of the composite catalyst includes: mixing the carrier and / or the molecular sieve with a cobalt source and grinding the mixture to obtain a mixed material; subjecting the mixed material to a melting treatment and a third calcination treatment; or, mixing the carrier or the molecular sieve with a cobalt source and grinding the mixture to obtain a mixed material; subjecting the mixed material to a melting treatment and a fourth calcination treatment to obtain a loaded material; mixing the loaded material with the unloaded carrier or the molecular sieve and subjecting the mixture to a grinding treatment and a molding treatment; optionally, the cobalt source is a solid cobalt source, and the cobalt source is selected from at least one of cobalt nitrates, sulfates, halides, nitrites, ammonium salts and acetates; preferably at least one of nitrates, nitrites and acetates.

[0030] According to the present invention, the conditions for the drying treatment may include: a temperature of 30 to 60°C, preferably 35 to 45°C; a time of 6 to 48 hours, preferably 12 to 24 hours; the calcination atmosphere of the third calcination treatment may be one of nitrogen, air and a reducing atmosphere; the conditions for the third calcination treatment may include: a temperature of 350 to 650°C, preferably 350 to 450°C; a time of 2 to 8 hours, preferably 4 to 6 hours; the calcination atmosphere of the fourth calcination treatment may be one of nitrogen, air and a reducing atmosphere; the conditions for the fourth calcination treatment may include: a temperature of 300 to 600°C, preferably 350 to 450°C; a time of 2 to 8 hours, preferably 4 to 6 hours.

[0031] A second aspect of the present invention provides a method for Fischer-Tropsch synthesis reaction, wherein the catalyst used in the method for Fischer-Tropsch synthesis reaction includes the aforementioned composite catalyst.

[0032] According to the present invention, the Fischer-Tropsch synthesis reaction method may include: mixing a catalyst with quartz sand and loading the mixture into a reactor, reducing the catalyst in situ, and introducing synthesis gas for synthesis reaction; wherein the synthesis gas may include H2 and CO, the volume ratio of H2 to CO may be 1 to 2, and the conditions of the synthesis reaction may include: a temperature of 200 to 250°C, a pressure of 1.5 to 4 MPa, and a volume space velocity of 1000 to 10000 h -1 , wherein the volume space velocity is based on the catalyst. Optionally, the reducing gas used in the in-situ reduction is hydrogen, and the temperature of the in-situ reduction is 300-500°C.

[0033] The present invention is further described below by way of examples, but the present invention is not limited thereto.

[0034] Example 1

[0035] (1) Preparation of supported cobalt-based catalyst: Weigh 10g Al2O3 powder, calculate the required mass of deionized water according to the water absorption rate and theoretical loading, fully dissolve cobalt nitrate hexahydrate in deionized water, and then use the impregnation solution to saturate Al2O3 powder. After aging at room temperature for 12 hours, dry and calcine, and the obtained catalyst is named Co / Al2O3. The drying method is forced air drying, the drying temperature is 120°C, and the drying time is 12 hours; the calcination atmosphere is nitrogen, the calcination temperature is 400°C, and the calcination time is 6 hours.

[0036] (2) Preparation of composite bifunctional catalyst: Co / Al2O3 powder and NaY molecular sieve powder were physically mixed in a ratio of 1:1, ground evenly in a mortar, and then tableted and crushed and sieved into 40-60 mesh to obtain the final catalyst named Co / Al2O3-YA.

[0037] Example 2

[0038] (1) The preparation method of the supported cobalt-based catalyst is the same as that in Example 1.

[0039] (2) Preparation of composite bifunctional catalyst: Co / Al2O3 powder and NaY molecular sieve powder were respectively tableted and crushed to 40-60 mesh, and then the two particles were physically mixed in a mass ratio of 1:1 to obtain the final catalyst named Co / Al2O3-YB.

[0040] Example 3

[0041] (1) Preparation of composite carrier: Al2O3 powder and NaY molecular sieve powder were physically mixed in a ratio of 1:1, ground evenly in a mortar, and then tableted and crushed and sieved into 40-60 mesh to obtain a composite carrier named Al2O3+Y.

[0042] (2) Preparation of composite bifunctional catalyst: Weigh 10g Al2O3+Y powder, calculate the required mass of deionized water according to the water absorption rate and theoretical loading, fully dissolve cobalt nitrate hexahydrate in deionized water, and then use the impregnation solution to saturate Al2O3+Y powder, age at room temperature for 12 hours, and then dry and calcine. The obtained catalyst is named Co / (Al2O3+Y). The drying method is forced air drying, the drying temperature is 120℃, and the drying time is 12 hours; the calcination atmosphere is nitrogen, the calcination temperature is 400℃, and the calcination time is 6h.

[0043] Example 4

[0044] (1) Preparation of supported molecular sieves: Weigh 10 g of NaY molecular sieve, calculate the required mass of deionized water according to the water absorption rate and theoretical loading amount, fully dissolve cobalt nitrate hexahydrate in deionized water, and then use the impregnation solution to saturate the NaY molecular sieve, age it at room temperature for 12 hours, and then dry and calcine it. The resulting catalyst is named Co / Y. The drying method is forced air drying, the drying temperature is 120°C, and the drying time is 12 hours; the calcination atmosphere is nitrogen, the calcination temperature is 400°C, and the calcination time is 6 hours.

[0045] (2) Preparation of composite bifunctional catalyst: Co / Y powder and Al2O3 powder were physically mixed in a ratio of 1:1, ground evenly in a mortar, and then tableted and crushed and sieved into 40-60 mesh to obtain the final catalyst named Co / Y-Al2O3.

[0046] Example 5

[0047] (1) Preparation of supported cobalt-based catalyst: Weigh 10 g of Al2O3 powder, mix cobalt nitrate hexahydrate with Al2O3 powder, grind evenly in a mortar or ball mill, and place the obtained solid in a sealed container in an oven or muffle furnace for melting and calcination. The obtained catalyst is named Co / Al2O3-A. The melting temperature is 60°C and the melting time is 30 hours. The molten solid is calcined at high temperature in a nitrogen atmosphere at a temperature of 400°C and a calcination time of 6 hours.

[0048] (2) Preparation of composite bifunctional catalyst: Co / Al2O3 powder and NaY molecular sieve powder were physically mixed in a ratio of 1:1, ground evenly in a mortar, and then tableted and crushed and sieved into 40-60 mesh to obtain the final catalyst named Co / Al2O3-YC.

[0049] Example 6

[0050] (1) Preparation of supported cobalt-based catalyst: Weigh 10g TiO2 powder, calculate the required mass of deionized water according to the water absorption rate and theoretical loading, fully dissolve cobalt nitrate hexahydrate in deionized water, and then use the impregnation solution to saturate the TiO2 powder. After aging at room temperature for 12 hours, dry and calcine the obtained catalyst, which is named Co / TiO2. The drying method is forced air drying, the drying temperature is 120°C, and the drying time is 12 hours; the calcination atmosphere is nitrogen, the calcination temperature is 400°C, and the calcination time is 6 hours.

[0051] (2) Preparation of composite bifunctional catalyst: Co / TiO2 powder and NaY molecular sieve powder were physically mixed in a ratio of 1:1, ground evenly in a mortar, and then tableted and crushed and sieved into 40-60 mesh to obtain the final catalyst named Co / TiO2-Y.

[0052] Example 7

[0053] (1) The preparation method of the supported cobalt-based catalyst is the same as that in Example 1.

[0054] (2) Preparation of composite bifunctional catalyst: Co / Al2O3 powder and ZSM-5 molecular sieve powder were physically mixed in a ratio of 1:1, ground evenly in a mortar, and then tableted and crushed and sieved into 40-60 mesh to obtain the final catalyst named Co / Al2O3-ZA.

[0055] Comparative Example 1

[0056] Weigh 10g of Al2O3 powder, calculate the required mass of deionized water according to the water absorption rate and theoretical loading, fully dissolve cobalt nitrate hexahydrate in deionized water, and then use the impregnation solution to saturate the Al2O3 powder. After aging for 12 hours at room temperature, dry and calcine, and the obtained catalyst is named Co / Al2O3. The drying method is forced air drying, the drying temperature is 120℃, and the drying time is 12 hours; the calcination atmosphere is nitrogen, the calcination temperature is 400℃, and the calcination time is 6h.

[0057] Test Example 1

[0058] The components of the catalysts prepared in Examples 1 to 7 and Comparative Example 1 were tested by X-ray fluorescence spectrometer (XRF). The test results are shown in Table 1. The "cobalt element / wt%" in Table 1 represents the content of cobalt element based on the total amount of the composite catalyst; the "weight ratio of carrier to molecular sieve" represents the weight ratio of the unloaded carrier and the unloaded molecular sieve added during the preparation of the composite catalyst.

[0059] Table 1

[0060]

[0061]

[0062] Test Example 2

[0063] 1.0g of each catalyst (20-60 mesh) prepared in Examples 1 to 7 and Comparative Example 1 was taken and mixed with quartz sand of the same mesh size at a ratio of 1:20, and then loaded into a fixed bed reactor. The inner diameter of the reaction tube used was 15mm and the length of the constant temperature zone was 60mm. The catalyst was then reduced in situ, the gas was pure hydrogen, the reduction temperature was 400℃, and the reduction time was 10h; the H2 / CO ratio in the Fischer-Tropsch reaction raw gas was 2, the reaction temperature was 250℃, the reaction pressure was 2MPa, and the reaction volume space velocity was 4000h -1 The raw gas and the reaction gas phase products were analyzed online by Agilent 990 gas chromatograph, and the liquid phase products were collected by hot trap and cold trap, separated, weighed and then analyzed offline. All performance evaluation results are shown in Table 2.

[0064] Table 2

[0065]

[0066]

[0067] It can be seen from the data in Table 2 that the composite catalysts prepared in Examples 1 to 7 have improved Fischer-Tropsch synthesis activities compared to Comparative Example 1. The Fischer-Tropsch active site and the acid site of Example 1 are closer, which may cause the Fischer-Tropsch product just generated at the Fischer-Tropsch active site to be more easily cracked and isomerized at the acid site, thereby promoting the improvement of diesel selectivity.

[0068] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0069] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0070] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A composite catalyst for Fischer-Tropsch synthesis reaction, characterized in that: The composite catalyst comprises cobalt element, a carrier and a molecular sieve; the cobalt element is loaded in the carrier and / or the molecular sieve; The carrier is an oxide carrier; the weight ratio of the carrier to the molecular sieve is 0.1 to 15; and the content of cobalt element is 5 to 40 wt % based on the total amount of the composite catalyst.

2. The composite catalyst according to claim 1, wherein The weight ratio of the carrier to the molecular sieve is 0.1 to 12, preferably 0.2 to 6; based on the total amount of the composite catalyst, the content of cobalt element is 5 to 32 wt%, preferably 8 to 25 wt%.

3. The composite catalyst according to claim 1, wherein The carrier is selected from at least one of SiO2, TiO2 and Al2O3; the molecular sieve is selected from at least one of NaY molecular sieve, ZSM-5 molecular sieve, ZSM-22 molecular sieve and SBA-15 molecular sieve, preferably NaY molecular sieve; optionally, the NaY molecular sieve has a SiO2 / Al2O3 ratio of 4 to 10 and a specific surface area of ​​500 to 800 m 2 / g.

4. The composite catalyst according to any one of claims 1 to 3, wherein The composite catalyst comprises a supported catalyst and the molecular sieve; the supported catalyst comprises the carrier and the cobalt element supported in the carrier.

5. The composite catalyst according to claim 1, wherein The composite catalyst is a granular catalyst, and the particle size of the granular catalyst is 10 to 80 μm.

6. The composite catalyst according to claim 1, wherein The preparation method of the composite catalyst comprises: placing the carrier and the molecular sieve in a solution containing a cobalt salt for impregnation to obtain an impregnated material; aging the impregnated material, drying it and performing a first calcination treatment; or placing the carrier or the molecular sieve in a solution containing a cobalt salt for impregnation to obtain an impregnated material; aging the impregnated material, drying it and performing a second calcination treatment to obtain a loaded material; mixing the loaded material with the carrier or the molecular sieve that has not been loaded, and then performing a grinding treatment and a molding treatment; Optionally, the cobalt salt is selected from at least one of cobalt nitrate, sulfate, halide, nitrite, ammonium salt and acetate; preferably at least one of cobalt nitrate, nitrite and acetate.

7. The composite catalyst according to claim 6, wherein The impregnation is saturated impregnation; The aging conditions include: a temperature of 30 to 60°C, preferably 35 to 45°C; a time of 6 to 48 hours, preferably 12 to 24 hours; The drying conditions include: a temperature of 80 to 150°C, preferably 90 to 120°C; a time of 6 to 48 hours, preferably 12 to 24 hours; The first calcination treatment is carried out in a nitrogen or air atmosphere, and the conditions of the first calcination treatment include: a temperature of 300-600°C, preferably 350-450°C; a time of 2-10 hours, preferably 4-6 hours; the second calcination treatment is carried out in a nitrogen or air atmosphere, and the conditions of the second calcination treatment include: a temperature of 300-600°C, preferably 350-450°C; a time of 2-10 hours, preferably 4-6 hours.

8. The composite catalyst according to claim 1, wherein The preparation method of the composite catalyst comprises: mixing the carrier and the molecular sieve with a cobalt source and then grinding the mixture to obtain a mixed material; melting the mixture and performing a third calcination process; or, mixing the carrier or the molecular sieve with a cobalt source and then grinding the mixture to obtain a mixed material; melting the mixture and performing a fourth calcination process to obtain a loaded material; mixing the loaded material with the carrier or the molecular sieve that has not been loaded and then grinding and molding the mixture; Optionally, the cobalt source is a solid cobalt source, and the cobalt source is selected from at least one of cobalt nitrate, sulfate, halide, nitrite, ammonium salt and acetate; preferably at least one of cobalt nitrate, nitrite and acetate.

9. The composite catalyst according to claim 8, wherein The conditions of the melt treatment include: a temperature of 40 to 90°C, preferably 50 to 70°C; a time of 24 to 60 hours, preferably 30 to 48 hours; The calcination atmosphere of the third calcination treatment is one of nitrogen, air and reducing atmosphere; the conditions of the third calcination treatment include: temperature of 300-600°C, preferably 350-450°C; time of 2-8h, preferably 4-6h; the calcination atmosphere of the fourth calcination treatment is one of nitrogen, air and reducing atmosphere; the conditions of the fourth calcination treatment include: temperature of 300-600°C, preferably 350-450°C; time of 2-8h, preferably 4-6h.

10. A method for Fischer-Tropsch synthesis reaction, characterized in that: The catalyst used in the Fischer-Tropsch synthesis reaction method includes the composite catalyst described in any one of claims 1 to 9.

11. The method according to claim 10, wherein: The Fischer-Tropsch synthesis reaction method comprises: mixing the catalyst with quartz sand and then loading the mixture into a reactor, reducing the catalyst in situ, and then introducing synthesis gas for synthesis reaction; wherein the synthesis gas comprises H2 and CO, the volume ratio of H2 to CO is 1 to 2, and the conditions of the synthesis reaction include: temperature of 200 to 250°C, pressure of 1.5 to 4 MPa, and volume space velocity of 1000 to 10000 h -1 ; Optionally, the reducing gas used in the in-situ reduction is hydrogen, and the temperature of the in-situ reduction is 300-500°C.

Citation Information

Patent Citations

  • Composite carrier-supported cobalt-based Fischer-Tropsch synthesis catalyst, and preparation method and application thereof

    CN104874417A

  • Productive middle-distillate hydrocracking catalyst and preparation method thereof

    CN106669781A

  • Catalyst for preparing low-carbon olefin from synthesis gas and preparation method and use method thereof

    CN111266131A

  • Catalyst for fischer-tropsch synthesis and method for preparing the same, and method for preparing modified molecular sieve carrier

    US20160045903A1

  • Fischer-tropsch process in the presence of a catalyst prepared from a molten salt

    US20200070129A1